Pengaruh Diklat Karyawan, Kemampuan Karyawan dan Komunikasi terhadap Kinerja Karyawan Pada PT. Pln (Persero) Area Pelayanan dan Jaringan Sidoarjo - Kafit, Moh. Ali Al; Saputri, Rizka Dibi Arryanti (Jurnal Informatika Ekonomi Bisnis, 2023)
Human resources are very important for companies in managing, organizing and utilizing employees so that they can function productively to achieve company goals. This study aims to analyze employee training, skills, and communication simultaneously influence the performance of employees at PT. PLN (Persero) Sidoarjo Service Area and Network. So that the formulation of the problem is whether Employee Training, Capability, and Communication have a simultaneous and partial effect on the performance of employees at PT. PLN (Persero) Sidoarjo Service Area and Network. The population in this study is the number of employees totaling 177 people at PT. PLN (Persero) Sidoarjo Service and Network Area in 2012. The sample used was the number of respondents taken as many as 64 respondents as the limit of employees in all divisions at PT. PLN (Persero) Sidoarjo Service Area and Network. Based on the results of calculations using multiple linear regression analysis techniques, namely that simultaneously using the F test shows a significant influence between the three variables (6.094 Fcount and 2.758 Ftable). Employee training variables partially do not have a significant effect on employee performance. The ability variable partially has no significant effect on employee performance. Communication variable has a significant and positive effect on employee performance. The independent variable that has the greatest influence on employee performance is communication, because the independent variable employee training and the independent variable ability do not have a significant effect on performance.